Discovery of a cis-regulatory element SaeM involved in dynamic regulation of synergid-specific MYB98 - Adhikari, Prakash Babu; Zhu, Shaowei; Liu, Xiaoyan; Huang, Chen; Xie, Liyang; Wu, Xiaoyan; He, Jiale; Mitsuda, Nobutaka; Peters, Benjamin; Brownfield, Lynette; Nagawa, Shingo; Kasahara, Ryushiro Dora (Frontiers in Plant Science, 2023)
MYB98 is a key regulator of the genetic network behind pollen tube attraction toward the female gametophyte. MYB98 is specifically expressed in the synergid cells (SCs), a female gametophyte component cells specialized for pollen tube attraction. However, it had not been clear how exactly MYB98 achieves this specific expression pattern. In the current study, we have determined that a normal SC-specific expression of MYB98 is dependent on a 16-bp-long cis-regulatory element, CATTTACACATTAAAA, freshly named as the “Synergid-specificActivationElement ofMYB98” (SaeM). An 84 bp fragment harboring SaeM in the middle was sufficient to drive exclusively SC-specific expression. The element was present in a significantly large proportion of SC-specific gene promoters and in the promoter of MYB98 homologous genes in the Brassicaceae (pMYB98s). Significance of such family-wide SaeM-like element conservation in exclusive SC-specific expression was confirmed by the Arabidopsis-like activation feature of Brassica oleracea–derived pMYB98 and absence of such feature of pMYB98 derived from a non-Brassicaceae member Prunus persica. Additionally, the yeast-one-hybrid assay showed that the SaeM can be recognized by ANTHOCYANINLESS2 (ANL2) and DAP-seq data further suggested for additional three ANL2 homologs targeting the similar cis-element. Overall, our study has concluded that SaeM plays a crucial role in driving exclusively SC-specific expression of MYB98 and strongly suggests for the involvement of ANL2 and its homologs in its dynamic regulation in planta. Future study on the transcription factors is expected to shed more light on the mechanism behind the process.